2010
DOI: 10.1111/j.1751-7141.2009.00065.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Executive Functioning Is Associated With Poorer Outcome in Cardiac Rehabilitation

Abstract: Patients with cardiovascular disease and cognitive impairment show reduced adherence to treatment. No study has examined whether cognitive impairment may also predict reduced benefit from cardiac rehabilitation (CR). It appears that cognitively impaired patients may exhibit poorer adherence to CR and limited gains in cardiovascular fitness and/or quality of life (QOL). Forty‐four older adults who enrolled in a CR program and completed measures at enrollment and discharge were included. Cognitive functioning wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 20 publications
1
16
0
1
Order By: Relevance
“…Studies on CF evaluation in stroke, however, have either excluded participants with cognitive impairment 8,13 or they did not specifically evaluate cognitive function. 6,11,12 Given that cognitive impairment is present after 65% to 82% of all strokes 17,18 and seems to influence rehabilitation outcomes, [19][20][21][22][23] it would appear prudent to evaluate the reliability of CF tests in stroke individuals with cognitive impairment.…”
Section: ª 2013 By the American Congress Of Rehabilitation Medicinementioning
confidence: 99%
“…Studies on CF evaluation in stroke, however, have either excluded participants with cognitive impairment 8,13 or they did not specifically evaluate cognitive function. 6,11,12 Given that cognitive impairment is present after 65% to 82% of all strokes 17,18 and seems to influence rehabilitation outcomes, [19][20][21][22][23] it would appear prudent to evaluate the reliability of CF tests in stroke individuals with cognitive impairment.…”
Section: ª 2013 By the American Congress Of Rehabilitation Medicinementioning
confidence: 99%
“…Although several mechanisms (e.g., cardiovascular risk reduction, added medical surveillance) may account for the survival advantage, a moderate-to-high exercise capacity has been shown to be inversely related to mortality in patients with ST-elevation myocardial infarction treated with emergent coronary angioplasty [34]. However, clinical depression [47], cognitive impairment [54], or both are associated with less favorable improvement in exercise tolerance after cardiac rehabilitation.…”
Section: Benefits/outcomesmentioning
confidence: 99%
“…However, recent studies have shown that older adults with lower cognitive function (reduced executive functioning) were less adherent to a 3-month exercise-based cardiac rehabilitation program. Importantly, participants with low adherence had poorer outcomes following their exercise intervention (9). Similarly, Tiedemann et al demonstrated that impaired global cognitive function (assessed using the Mini-Mental State Examination) was a significant independent predictor of low physical activity adherence during a 6–12 month intervention among older retirement village residents (10).…”
Section: Introductionmentioning
confidence: 99%